Evaluation of The Implementation Process of The “Virtue Diary” Book in Improving Student Character ODD - Kurniati Kurniati; Hasto Bramantyo; Mettadewi Wong (Jurnal Mamangan, 2023)
Character education at the elementary school level serves as a crucial foundation in shaping students’ character from an early age. One of the initiatives implemented to support this goal is the Diary Kebajika program, which involves recording daily good deeds as a form of self-reflection. This study aims to analyze the implementation of the Diary Kebajikan in character education at SD Sivaliputta, focusing on the process of implementation, supporting and inhibiting factors, as well as the improvement of students’ moral conduct. This research employed a qualitative approach with a case study method. The research subjects included the principal, teachers, parents, and students. Data were collected through in-depth interviews, participatory observation, and written and visual documentation. Data analysis was conducted using the stages of data reduction, data presentation, and conclusion drawing, combined with the CIPP evaluation model (Context, Input, Process, Product), ensuring that the findings were not only descriptive but also interretative. The results indicate that the Diary Kebajikan program was effectively implemented due to the support of teachers, the involvement of parents, and the enthusiasm of students. The program successfully fostered honesty, discipline, care, politeness, and respect toward teachers and parents, reflected both at school and at home. Obstacles such as students’ negligence in writing or limited reading ability were addressed through teachers’ guidance and parental assistance. Interpretatively, the success of the program lies not only in the diary itself but also in the synergy among schools, families, and the learning environment, as emphasized in the educational philosophy of Ki Hajar Dewantara. Furthermore, the program aligns with Buddhist teachings through the Buddhist Five Precepts, the Sigalovada Sutta, and the cultivation of the Brahmavihāras. Thus, the Diary Kebajika contributes as a model of character education based on daily reflection that is contextual, religious, and sustainable in elementary education